Analisis Sisa Cadangan Reservoir Pada Sumur X Lapangan Y - Priska Vernanda Hipui; Jan Friadi Sinaga; Mirza; Baiq Maulinda Ulfah; Mohammad Lutfi; Luthfiyah Atisa Fadhilah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2021)
Decline curve analysis: this method uses an exponential decline curve to describe the decline in reservoir production over time. This method utilizes historical production data to extrapolate and estimate the remaining reserves in the reservoir. So that the well in the field "Y" can be predicted using the decline curve. Trial Error and X2 Chi-Square Test method and obtained the value of the b exponent, namely 0 type decline curve Exponential, rate of decline (Di) 0.018616 and the smallest value of ∑X2 are 136.614. EUR is 1630,727 BOPD and ERR to limit is 1794,672 BOPD. The remaining production life is 136 months or 11 years.